The Role of Greed in Moderating Factors That Enhance Investment Decisions - NOSITA, Firda; MOELJADI, Moeljadi; SUMIATI, Sumiati; RATNAWATI, Kusuma (Theoretical and Practical Research in Economic Fields, 2025)
The study aims to empirically test the effects of risk tolerance, social networks and financial literacy on individual investment decisions in the Ponzi scheme in Indonesia. In this study, greed is used as a moderating variable. A questionnaire distributed online obtained a total sample of 402 individual investors who were or had invested in the Ponzi Scheme. Data was analyzed with structural equation modelling-partial least square (SEM-PLS). The results demonstrate that risk tolerance, social networks and financial literacy affect individual investment decision-making in the Ponzi scheme. Meanwhile, greed does not moderate the relationship between risk tolerance, social network and financial literacy in individual decision-making in a Ponzi scheme. The findings of this study confirm that risk tolerance drives individuals to invest in risky schemes such as Ponzi. Risk-tolerant individuals tend to take the opportunity to make money from the Ponzi scheme. Social networks are also shown to have a significant effect on individual investment decisions in Ponzi schemes. Information obtained by the individuals through interactions with their social environment, both face-to-face and social media, strengthens the intention to join Ponzi scheme investments. Meanwhile, good financial literacy makes individuals more optimistic and confident to invest in Ponzi. Greed does not moderate the effects of risk tolerance, social networks and financial literacy on individual investment decisions in a Ponzi scheme.